Analysis of Junior High School Students' Mathematical Problem-Solving Skills on Integers and Fractions Material Viewed from Learning Interest - Zamroni Aza; Agus Subaidi (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2024)
Problem-solving skills are essential for students to possess, as these skills make it easier for them to learn the relevance of mathematics to other subjects and in real-life situations. However, there is diversity in problem-solving abilities among students. This is influenced by several factors, such as learning interest. Therefore, it is crucial to further understand the differences in students' problem-solving abilities. This study aims to describe the mathematical problem-solving abilities of junior high school students on the material of integers and fractions, viewed from learning interest. The research method used is qualitative research with data collection techniques using learning interest questionnaires, problem-solving ability tests, interviews, and documentation. The research subjects were 3 seventh-grade students of SMPN 1 Pragaan with each having high, medium, and low learning interest categories. Data analysis techniques include data reduction, data presentation, and conclusions. Meanwhile, to check the validity of the data, time triangulation was used. The results showed that students with high learning interest in solving integer and fraction problems were identified as fulfilling all indicators of problem-solving ability, including understanding the problem, planning the solution, solving the problem according to the plan, and checking back. While students with moderate learning interest fulfilled the indicators of carrying out the plan and checking the solution of the problem in the question, and students with low learning interest in solving integer and fraction problems were identified as not fulfilling all 4 indicators of problem-solving ability.